Age-related differences in psychosocial risks among community mental health professionals - Coral Oliver; Irene Aliagas; Irene Mínguez-García; Inmaculada Mateo-Rodríguez; Eugenia González-de Molina; Elvira Pérez-Benítez (Frontiers in Psychology, 2026)
Introduction The progressive aging of the workforce poses important challenges for occupational health, particularly in emotionally demanding sectors such as community mental health services. Understanding age-related differences in psychosocial working conditions is crucial for promoting sustainable careers and successful aging at work. Objective and methods This study examines psychosocial risk factors across five age groups (18–25, 26–35, 36–45, 46–55, ≥56) among community mental health professionals in Spain ( N = 756). Psychosocial risks were assessed using a tailored instrument covering 13 factors, including: Leadership and communication, Interpersonal conflict at work, Work climate, Participation in decision-making, Organizational justice and recognition, Job stress, Work–family conflict, Role ambiguity, Work pace, Mental workload, Workplace violence, Job knowledge, and Work engagement. Age differences were analyzed using one-way ANOVAs with Bonferroni post hoc tests. Results Overall, high levels of mental workload and work pace were observed across the sample. Significant differences were found in interpersonal conflict, job stress, work pace, and workplace violence. Employees aged 26–35 reported the most favorable psychosocial profile. Younger employees (18–25) reported the highest levels of interpersonal conflict. Older employees (46–55 and ≥56) experienced higher job stress. Work pace was highest among employees aged 46–55, and exposure to workplace violence was lower compared to younger and mid-career workers. Conclusion These findings highlight age-related differences in psychosocial risks and underscore the need for age-sensitive organizational strategies in mental health care settings.